2017
DOI: 10.1002/ijop.12420
|View full text |Cite
|
Sign up to set email alerts
|

Catching up with wonderful women: The women‐are‐wonderful effect is smaller in more gender egalitarian societies

Abstract: Inequalities between men and women are common and well-documented. Objective indexes show that men are better positioned than women in societal hierarchies-there is no single country in the world without a gender gap. In contrast, researchers have found that the women-are-wonderful effect-that women are evaluated more positively than men overall-is also common. Cross-cultural studies on gender equality reveal that the more gender egalitarian the society is, the less prevalent explicit gender stereotypes are. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…This might have influenced the generally favor able feelings female targets received in this study. However, our findings are generally consistent with prior research that overall women are shown more favorable feelings than men (Krys et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This might have influenced the generally favor able feelings female targets received in this study. However, our findings are generally consistent with prior research that overall women are shown more favorable feelings than men (Krys et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Most of the work examining gender differences in empathy focus on the experiencer and find that women report greater empathy than men (e.g., Christov-Moore et al, 2014;Clarke, Marks, & Lykins, 2016). Though there is less work examining target gender differences, what there is indicates women receive more empathy than men (Oswald, 2000;Stuijfzand et al, 2016), in line with benevolent sexism (Glick & Fiske, SOCIAL DOMINANCE ORIENTATION AND EMPATHY 41 1996) and the general tendency to see women as morally superior and fundamentally pure (and perhaps therefore more deserving of empathy) than men (Eagly & Mladinic, 1994;Krys et al, 2018). Although previous research (Cikara et al, 2014) has documented intergroup (counter-) empathy bias between groups using both male and female targets, it is an open question whether SDO's modulation of these emotions will be as strong for female compared to male targets.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…For markers of country-level individualism, we obtained scores of individualism (Hofstede, 2001;Minkov et al, 2017), open society (Krys et al, 2019), affective and intellectual autonomy and embeddedness (Schwartz, 2008); following the formula for aggregating various cross-cultural scores of similar phenomenona (Krys et al, 2018). We also calculated a meta-factor score of individualism which is the mean of standardized values of the above markers of individualism.…”
Section: Methodsmentioning
confidence: 99%